Time Layers or Time Regimes - Jansen, Harry (História da Historiografia: International Journal of Theory and History of Historiography, 2024)
In this article, I examine Koselleck’s vision on time layers and the forward-looking view they entail. According to me, both its future orientation and its division into time layers are debatable, given his Kantian approach to concepts and his misappropriation of the simultaneity of the non-simultaneous. My research is quite urgent since several authors are following in his footsteps. Hartog does this by distinguishing between three time regimes, the second being based on Koselleck’s future-oriented time. Lucian Hölscher prefers Koselleck’s empty time to an embodied one. Zoltán Boldizsár Simon and Marek Tamm started a project in 2021 called ‘Historical Futures,’ in which they propose a time regime that decouples the past and present from the future. They have concluded it with a plea for an open future. In this way they hope to have a better starting point for dealing with the issues of the Anthropocene. Unfortunately, all of them sharpen Reinhart Koselleck’s vision of a forward-looking time and thus also reinforce its shortcomings. Hartog’s time regimes would have been a better choice. Thinking ahead and disconnecting the past and present from the future cannot solve our current time out of joint. A more balanced view of time is a better way out.